2023
DOI: 10.3389/fendo.2023.1289572
|View full text |Cite
|
Sign up to set email alerts
|

Serum iodine concentration and its associations with thyroid function and dietary iodine in pregnant women in the southeast coast of China: a cross-sectional study

Shumi Ji,
Xiaoyan Wu,
Jiani Wu
et al.

Abstract: BackgroundIodine deficiency is a major public health problem in pregnant women. Serum iodine (SI) may represent a useful biomarker for iodine nutrition evaluation. We aimed to assess the relationship between serum iodine concentration (SIC) and urinary iodine concentration (UIC), dietary iodine, thyroid function, and thyroid diseases in pregnant women in the southeast coast of China, and to provide a normal reference range of SIC for pregnant women.MethodsA multistage random sampling method was used to select … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…Notably, these ranges were observed in regions with adequate iodine nutrition for the general population as well as areas where iodine supplementation was implemented. The suitable range of SIC in this study was basically consistent with the research findings of Ji et al (6) The suitable 24-hour UIE value exceeded that reported in Saudi Arabia (28). The suitable of Tg were lower than those documented in many studies (29).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Notably, these ranges were observed in regions with adequate iodine nutrition for the general population as well as areas where iodine supplementation was implemented. The suitable range of SIC in this study was basically consistent with the research findings of Ji et al (6) The suitable 24-hour UIE value exceeded that reported in Saudi Arabia (28). The suitable of Tg were lower than those documented in many studies (29).…”
Section: Discussionsupporting
confidence: 91%
“…Among these studies, one conducted in Shanghai (China) displayed that both low and high urine iodine concentration was related to thyroid function and autoimmunity (5). A cross-sectional study in the southeast coast of China showed that serum iodine concentration (SIC) negatively correlated with thyroid stimulating hormone (TSH), and positively correlated with other thyroid function indicators, which indicating SIC may serve as a composite indicator of iodine nutritional status (6). A study conduct in northern Spain indicated that the consumption of iodized salt was associated with adequate iodine nutrition but not with maternal thyroid function (7).…”
Section: Introductionmentioning
confidence: 99%